Amlodipine effects on blood pressure, endothelial function, bronchial air flow, and quality of life in patients with arterial hypertension and chronic obstructive pulmonary disease - I. G. Fomina; A. E. Bragina; A. V. Vetluzhsky (Российский кардиологический журнал, 2005)
.